Organizational communication and performance appraisal: 360º feedback and organizational communication - Mourão, Rita Monteiro (2018)
Organizational communication and performance appraisal are essential to human resources management. Organizational communication has been relevant in organizations, especially because globalization and competitiveness create more permanent contact between employees (Miller, 2011). In turn, performance appraisal has been shown to be essential to organizational effectiveness (Proctor and Doukakis, 2003). However, traditional performance evaluation has some limitations (e.g. quotation mistakes associated with the subjectivity of evaluators) (Caetano, 2008). To prevent these limitations, it is important to be aware of 360º evaluation, a specific evaluation method that considers more than one appraiser (Brutus and Gorriti, 2005), and permits to control any eventual idiosyncrasies (Oh and Mount, 2011). This evaluation method is more frequent in organizations with a hierarchical structure of bottom-up (i.e., greater sharing of power) (Brutus and Brassard, 2005). It is expected that the 360º evaluation may be useful to create a better organizational communication, because communication failures tend to occur in organizations with a strong hierarchical structure, due to lower sharing of power among different organizational actors (Felts, 1992). In this case, we describe a theoretical review of these topics, because they have been rarely reported in literature and may be related to each other. In this way, we will present the results of interviews with two experts in the field of organizational communication. These results are important to define organizational communication and 360º evaluation and to create an analysis model about these topics.